LEVEL OF KNOWLEDGE REGARDING HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNE DEFICIENCY SYNDROME AND PEOPLE LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS AMONG HEALTH-CARE STUDENTS OF SELECTED COLLEGES IN CHENNAI - Mangeswari, Latha; KANNIAMMAL C; Mahendra, Jaideep (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of the study was to assess the level of knowledge among health-care students (HCS) toward human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) and people living with HIV (PLHIV) in dental and nursing colleges at Chennai. Methods: A quantitative approach and descriptive research design were adopted for the present study. HIV knowledge questionnaire-45 was used to assess the level of knowledge regarding HIV and PLHIV. Nonprobability convenient sampling technique was used for the selection of samples. Results: The collected data were analyzed using SPSS. Among 600 HCS, 274 (46%) had inadequate knowledge, 191 (32%) had moderately adequate knowledge, and about 135 (23%) students had adequate knowledge. The mean knowledge score was 10.94. Conclusion: HCS are in need of intense teaching program with various teaching methods which help to enhance their knowledge level and to eliminate the fear and stigma about handling of PLHIV. Keywords: The health-care students, Level of knowledge, Human immunodeficiency virus/Acquired immune deficiency syndrome, People living with human immunodeficiency virus.